Pemberdayaan Masyarakat Untuk Budidaya Jangkrik Sebagai Peluang Bisnis Tasikmalaya - Yudi Setia Rachmanda (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
The purpose of this community service activity is to provide an understanding of cricket cultivation to the community of Gununggede Village, Tasikmalaya City. This activity is an outreach to people who have the main resources in cricket cultivation so that they can create new businesses. Provision of equipment is also carried out to facilitate the process. The results of the activity showed the high enthusiasm of the participants. Participants who took part in this service activity proved to have great intentions in cricket cultivation. This is evidenced by the fact that one of the participants has implemented cricket cultivation as an additional means of income by marketing it to the bird market and feed shops.